Dupilumab attenuates the expression of TSLP and IL-8 induced by dsRNA and IL-4/IL-13 co-stimulation in human small airway epithelial cells - Aditya Sri Listyoko; Ryota Okazaki; Tomoya Harada; Genki Inui; Hiroki Kohno; Miyu Nishigami; Miki Takata; Masato Morita; Akira Yamasaki (PLoS ONE, 2026)
Background The interaction between viral components and type 1 or type 2 cytokines during asthma exacerbations in the airway epithelium may contribute to worsening inflammation. However, these interactions in the small airway epithelium—particularly those involving alarmins (TSLP, IL-25, and IL-33) and IL-8—remain unclear. Dupilumab, a biologic agent used in severe asthma, blocks IL-4 receptor alpha (IL-4Rα) and may offer therapeutic benefits in virus-induced asthma exacerbations. In this study, we evaluate the effects of double-stranded RNA (dsRNA), in combination with various cytokines and dupilumab, on the Human Small Airway Epithelial Cells (HSAECs) line. Methods Primary HSAECs were preincubated with dsRNA to induce the gene and protein expression of alarmins and IL-8. To evaluate the effects of cytokines on dsRNA-induced alarmin and IL-8 expression, various type 1 and type 2 cytokines were co-stimulated with dsRNA. Dupilumab was used as a pretreatment prior to co-stimulation with dsRNA and IL-4 or IL-13. Gene expression of TSLP, IL-25, IL-33, and IL-8 was assessed by quantitative PCR, and protein expression was evaluated by Western Blotting. Results dsRNA significantly increased the expression of TSLP and IL-8. IL-4 and IL-13 further enhanced dsRNA-induced TSLP and IL-8 gene and protein expression. In contrast, TNF-α reduced dsRNA-induced TSLP expression but enhanced IL-8 gene and protein expression. Dupilumab attenuated the expression of TSLP and IL-8 induced by co-stimulation with dsRNA and IL-4 or IL-13 in HSAECs. Conclusion In the microenvironment of small airway epithelial cells, particularly during viral infections, the presence of IL-4 or IL-13 may enhance the expression of TSLP and IL-8. Dupilumab attenuates this expression, potentially offering additional benefits in the treatment of asthma, especially during virus-induced asthma exacerbations.